The Influence Of Organizational Commitment, Professional Ethics On Auditor Performance With Professionalism As A Moderating Variable - Muhammad Yudhistira; Mustain Mustain (Journal of Accounting and Auditing, 2025)
Purpose – This study aims to analyze the influence of Organizational, Professional Ethics on Auditor Performance with Professionalism as a moderating variable. Design/methodology/approach – The study uses primary data with a sample of 35 respondents, selected through random sampling. The research employs quantitative methods to assess the relationships between the variables, analyzing the data to determine the impact on Auditor Performance. Findings – The results showed that Organizational Commitment has a significant positive effect on Auditor Performance. Professional Ethics has a positive but insignificant effect on Auditor Performance. Professionalism does not strengthen the relationship between Organizational Commitment to Auditor Performance. Professionalism does not strengthen the relationship between Professional Ethics on Auditor Performance. Research limitations/implications – The study is limited by its relatively small sample size of 35 respondents, which may impact the generalizability of the findings. Future research could expand the sample or explore additional variables to better understand the factors affecting Auditor Performance in various contexts.